US Veterans Show Improvements in Subjective but Not Objective Sleep following Treatment for Posttraumatic Stress Disorder: Secondary Analyses from a Randomised Controlled Trial - Mathersul, Danielle C.; Schulz-Heik, R. Jay; Avery, Timothy J.; Allende, Santiago; Zeitzer, Jamie M.; Bayley, Peter J. (Depression and Anxiety, 2023)
Background. Sleep disturbances are a prominent feature of posttraumatic stress disorder (PTSD), and poorer sleep quality is associated with higher PTSD severity. This highlights the importance of monitoring sleep outcomes alongside PTSD symptoms in treatments targeting PTSD. Yet few studies monitor both sleep and PTSD outcomes, unless sleep is the primary treatment target. Furthermore, inconsistencies remain about the effects of first-line, evidence-based PTSD treatments on sleep. Methods. Here, we explored changes in sleep in secondary analyses from a randomised controlled trial that originally assessed the noninferiority of a breathing-based yoga practice (Sudarshan kriya yoga; SKY) to a first-line PTSD treatment (cognitive processing therapy (CPT)) for clinically significant PTSD symptoms among US veterans (intent-to-treat N=85; per protocol N=59). Sleep was assessed via subjective (self-reported sleep diary), PTSD symptom severity items (self-reported and clinician-administered insomnia/nightmare sleep items), and objective (wrist actigraphy) measures. Results. Following treatment, subjective sleep diary measures of quality, latency, and wake duration showed small effect size (d=.24−.39) improvements, with no significant differences between treatment groups. Significant improvements were also observed in PTSD sleep symptoms, though CPT (d=.34) more reliably reduced nightmares while SKY (d = .44-.45) more reliably reduced insomnia. In contrast, there were no significant treatment-related effects for any of the actigraphy-measured sleep indices. Conclusions. To our knowledge, this is the first study to investigate sleep as an outcome of CPT or SKY for PTSD, across a combination of subjective diary, PTSD symptom severity, and objective actigraphic measures. Findings lend support to a growing body of evidence that trauma-focused psychotherapy for PTSD improves sleep and suggest that yoga-based interventions may also be beneficial for sleep among individuals with emotional or mental health disorders like PTSD. This trial is registered with NCT02366403.